Pengaruh Kompensasi dan Lingkungan Kerja terhadap Kinerja Karyawan dengan Motivasi Kerja sebagai Variabel intervening pada PT. Perkebunan Nusantara XII bagian Pengolahan Karet Kebun Kotta Blater Jember - Nurul Khoiriah; Sri Wahyu Lelly H.S.; Wiji Utami (e-Journal Ekonomi Bisnis dan Akuntansi, 2019)
This research entitled "The Influence of Compensation and Work Environment to employee’s Performance with work motivation as an intervening variable in PT. Perkebunan Nusantara XII Rubber Processing Department Plantation Kotta Blater Jember Jember ". This study aimed to analyze the influence of compensation and work environment to employee’s performance with work motivation as an intervening variable in PT. Perkebunan Nusantara XII rubber processing department plantation Kotta Blater Jember. The population in this research were all employees of PT Perkebunan Nusantara XII rubber processing department plantation Kotta Blater Jember. The sampling method used is saturated sample or census with the number of respondents as many as 34 people. Variables used as many as 4 variables. The analysis tool used is Path Analysis. The results showed that: 1) Compensation and work environment have a significant influence on work motivation in PTPN XII Plantation Kotta Blater Jember; 2) Compensation and work environment have a significant influence on the employee’s Performance in PTPN XII Plantation Kotta Blater Jember, and; 3) Motivation significant influence on the employee’s Performance in PTPN XII Plantation Kotta Blater Jember. Keywords: Compensation, Work Environment, Work Motivation and Employee Performance.